Duration-dependent effects of the BDNF Val66Met polymorphism on anodal tDCS induced motor cortex plasticity in older adults: a group and individual perspective - Puri, Rohan; Hinder, Mark R.; Fujiyama, Hakuei; Gomez, Rapson; Carson, Richard G.; Summers, Jeffery J. (Frontiers in Aging Neuroscience, 2015)
The brain derived neurotrophic factor (BDNF) Val66Met polymorphism and stimulation duration are thought to play an important role in modulating motor cortex plasticity induced by non-invasive brain stimulation (NBS). In the present study we sought to determine whether these factors interact or exert independent effects in older adults. Fifty-four older adults (mean age = 66.85 years) underwent two counterbalanced sessions of 1.5 mA anodal transcranial direct current stimulation (atDCS), applied over left M1 for either 10 min or 20 min. Single pulse transcranial magnetic stimulation (TMS) was used to assess corticospinal excitability (CSE) before and every 5 min for 30 min following atDCS. On a group level, there was an interaction between stimulation duration and BDNF genotype, with Met carriers (n =13) showing greater post-intervention potentiation of CSE compared to Val66Val homozygotes (n = 37) following 20 min (p = 0.002) but not 10 min (p = 0.219) of stimulation. Moreover, Met carriers, but not Val66Val homozygotes, exhibited larger responses to TMS (p = 0.046) after 20 min atDCS, than following 10 min atDCS. On an individual level, two-step cluster analysis revealed a considerable degree of inter-individual variability, with under half of the total sample (42%) showing the expected potentiation of CSE in response to atDCS across both sessions. Intra-individual variability in response to different durations of atDCS was also apparent, with one-third of the total sample (34%) exhibiting LTP-like effects in one session but LTD-like effects in the other session. Both the inter-individual (p = 0.027) and intra-individual (p = 0.04) variability was associated with BDNF genotype. In older adults, the BDNF Val66Met polymorphism along with stimulation duration appears to play a role in modulating tDCS-induced motor cortex plasticity. The results may have implications for the design of NBS protocols for healthy and diseased aged populations.